Thoracic Stent Graft Implantation for Aortic Coarctation with Patent Ductus Arteriosus via Retroperitoneal Iliac Approach in the Presence of Small Sized Femoral Artery. (3rd May 2016) - Korkmaz, Ozge; Beton, Osman; Goksel, Sabahattin; Kaya, Hakkı; Berkan, Ocal
Abstract : Endovascular stent graft implantation is a favorable method for complex aortic coarctation accompanied by patent ductus arteriosus. Herein, an 18-year-old woman with complex aortic coarctation and patent ductus arteriosus was successfully treated by endovascular thoracic stent graft via retroperitoneal approach. The reason for retroperitoneal iliac approach was small sized common femoral arteries which were not suitable for stent graft passage. This case is the first aortic coarctation plus patent ductus arteriosus case described in the literature which is treated by endovascular thoracic stent graft via retroperitoneal approach.